Ethics in Islamic Accounting Research: A Bibliometric Analysis and Review - Endah Sundari, Desy; Febriani , Dewi (Tazkia Islamic University College, 2023)
This study aims to determine the development and relevance of ethics in Islamic accounting. The data used in this study were 94 indexed research publications with the theme of Islamic Accounting for the period 2003 to 2022. The data were then processed and analyzed using the R Biblioshiny application program to determine the bibliometric map of the development of the role of ethics in Islamic accounting. The results show that the number of publications on the development of Islamic accounting research has increased significantly. The results showed that the journal with the highest productivity with the theme of Islamic accounting is the Islamic Accounting Journal. The authors who wrote the most were Kamla R and Yacoob H. “Accounting” became the longest trending topic until 2020 and “Islamic Accounting” became the most used topic in 2018.